Forest plantations with Toona ciliata: impacts of the managerial flexibility on economic viability - Munis, Rafaele Almeida [UNESP]; Camargo, Diego Aparecido [UNESP]; Simões, Danilo [UNESP] (CIRAD (Centre de Cooperation Internationale en Recherche Agronomique Pour le Developpement), 2022)
Forest plantations with Toona ciliata are presented as economically viable thanks to the suitability of their wood for high-quality niche products. Howe-ver, this study verifies whether investment projects in T. ciliata plantations are economically viable with the incorporation of managerial flexibility. We apply technical-economic coefficients from T. ciliata forest plantations over a 15-year planning horizon, considering the investment project as an underlying asset and the price of wood as the only source of uncertainty. Using the Monte Carlo method, we model uncertainty to obtain project volatility, so that, using the Real Option Approach, managerial flexibility for deferral, expansion and abandonment is added to the underlying assets. Based on the traditional economic valuation methodology, we obtained a static net present value of USD 5,075, which reflects the economic viability of the investment project in T. ciliata forest plantations. Due to the uncertainty ari-sing from timber prices, project volatility was 131.7%. Afterwards, it was found that incorporating the deferral and abandonment options added a premium of USD 2,147 to the value of the project, redirecting it towards an expanded net present value of USD 7,223. Incorporation of the real deferral and abandonment options provides flexibility and support for the decision-making process in the management of T. ciliata forest plantations, resulting in a 42.3% increase in the value of the investment project.
Plantaciones forestales con Toona ciliata: impacto de la flexibilidad de la gestión en su viabilidad económica
Plantations forestières de Toona ciliata: impacts de la gestion flexible sur leur viabilité économique
Keywords: Australian cedar; binomial trees; biological asset; dynamic modelling; forest investment; Net Present Value; Real Option Approach; volatility